Pengaruh Forgiveness pada Agresivitas Remaja di Kecamatan Johar Baru: Penelitian - Mikaela Berliyana Alitani; Yeny Duriana Wijaya; Kamalia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Adolescent aggression is a social problem that is still commonly found in densely populated urban areas, one of which is Johar Baru District, Central Jakarta. Social environments full of conflict and experiences of violence make adolescents vulnerable to aggressive behavior. One psychological factor suspected to play a role in reducing aggressiveness is forgiveness. This study aims to examine the effect of forgiveness on aggressiveness in adolescents in Johar Baru District. The study used a quantitative approach with a survey method. Participants were 100 adolescents aged 10–17 years selected using a purposive sampling technique. The research instruments included the Forgiveness Scale based on McCullough's concept and the Aggressiveness Scale adapted from Buss and Perry. Data analysis used the Spearman correlation test. The results showed a significant negative relationship between forgiveness and aggressiveness (ρ = -0.419; p < 0.05). This finding indicates that the higher the level of forgiveness, the lower the level of aggressiveness in adolescents. This study emphasizes the importance of strengthening forgiveness as a psychological intervention strategy to reduce adolescent aggressiveness in conflict-prone environments..